Gaucher Disease and iPSCs: what does the future hold? - Amaral, Olga (2020)
Introduction: Currently we are working with induced pluripotent stem cells (iPSCs) in order to generate cells with the same genetic background as the donor patients and further differentiate them in cell types of interest for the study of specific diseases. We are manipulating human skin fibroblasts and have included multiple checkpoints along the procedures to avoid potential pitfalls.